"Chciwiec na wydawnictwa z zakresu przyrodoznawstwa”. Lwowski nauczyciel Jan Smetański i fragment jego kolekcji w Bibliotece Śląskiej w Katowicach - Weronika Pawłowicz (Z Badań nad Książką i Księgozbiorami Historycznymi, 2020)
Jan Smetanski (1881-1959), a Lviv natural historian and a high school teacher, was an avid bibliophile. He assembled a rich collection of 40,000 volumes, which was removed from Lviv after the war and located first in Przemysl and then in Katowice. After the owner died, the collection was dispersed. Some of the books were purchased by the Institute of Zoology of the Polish Academy of Sciences in Warsaw, a part by the Silesian Library in Katowice, a fragment of the collection remained in the possession of the family. The article discusses a fragment of Jan Smetanski’s collection kept in the collections of the Silesian Library.